(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of in-house training on knowledge and implementation of nursing rounds in the inpatient ward of the 03.06.01 Ciremai Hospital, Cirebon. The method used is quantitative with a quasi-experimental design and a pre-experimental approach and a one group pre and post design. The results of the study showed that the description of respondents’ knowledge of nursing rounds before in-house training with an average value of 56.98, while the average value after in-house training was carried out, nurses’ knowledge of nursing rounds was 74.58. The description of the implementation of nursing rounds before in-house training with an average value of 58.02, while the average value after in-house training was almost 65.43. In conclusion, there is an effect of in-house training on knowledge and implementation of nursing rounds in the inpatient ward of the 03.06.01 Ciremai Hospital, Cirebon. Keywords: In-House Training, Knowledge, Nursing Rounds.